Production of MSTN‐mutated cattle without exogenous gene integration using CRISPR‐Cas9. Issue 7 (22nd July 2021) - Gim, Gyeong‐Min; Kwon, Dong‐Hyeok; Eom, Kyeong‐Hyun; Moon, JoonHo; Park, Ji‐Hyun; Lee, Won‐Wu; Jung, Dae‐Jin; Kim, Dae‐Hyun; Yi, Jun‐Koo; Ha, Jae‐Jung; Lim, Ka‐Yeong; Kim, Jin‐Soo; et al.
Abstract: Many genome‐edited animals have been produced using clustered regularly interspaced short palindromic repeats (CRISPR)‐Cas9 technology to edit specific genes. However, there are few guidelines for the application of this technique to cattle. The goal of this study was to produce trait‐improved cattle using the genome‐editing technology CRISPR–Cas9. Myostatin ( MSTN ) was selected as a target locus, and synthetic mRNA of sgRNA and Cas9 were microinjected into fertilized bovine embryos in vitro. As a result, 17 healthy calves were born, and three of them showed MSTN mutation rates of 10.5%, 45.4%, and 99.9%, respectively. Importantly, the offspring with the 99.9% MSTN mutation rate had a biallelic mutation (‐12 bps) and a double‐muscling phenotype. In conclusion, we demonstrate that the genome‐editing technology CRISPR‐Cas9 can produce genetically modified calves with improved traits. Graphical Abstract and Lay Summary: Myostatin (MSTN) is known to regulate skeletal muscle growth inhibition. In this work, we demonstrated optimal conditions for CRISPR‐Cas9 systems that efficiently produce MSTN mutant bovine embryos. Based on the protocol, healthy MSTN mutated calves were successfully delivered. This study will help us develop improved genetic traits in cattle and contribute to the advance of genetic breeding in agricultural science.